2013
DOI: 10.1177/0954411912472845
|View full text |Cite
|
Sign up to set email alerts
|

Effect of simplifications of bone and components inclination on the elastohydrodynamic lubrication modeling of metal-on-metal hip resurfacing prosthesis

Abstract: ReuseUnless indicated otherwise, fulltext items are protected by copyright with all rights reserved. The copyright exception in section 29 of the Copyright, Designs and Patents Act 1988 allows the making of a single copy solely for the purpose of non-commercial research or private study within the limits of fair dealing. The publisher or other rights-holder may allow further reproduction and re-use of this version -refer to the White Rose Research Online record for this item. Where records identify the publish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…A significant amount of research has been undertaken on the EHL of artificial hip joints . In these models, the interaction of the fluid film pressure and the elastically deformable head and cup is calculated to predict both the film thickness and the lubricating fluid pressure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant amount of research has been undertaken on the EHL of artificial hip joints . In these models, the interaction of the fluid film pressure and the elastically deformable head and cup is calculated to predict both the film thickness and the lubricating fluid pressure.…”
Section: Introductionmentioning
confidence: 99%
“…A significant amount of research has been undertaken on the EHL of artificial hip joints. [1][2][3][4][5][6][7][8][9][10][11][12][13] In these models, the interaction of the fluid film pressure and the elastically deformable head and cup is calculated to predict both the film thickness and the lubricating fluid pressure. Such studies have shown that the fluid-filled lubricating gap is at nanometer size-an extremely small gap when compared to typical engineering bearing problems, where the fluid-filled gap is typically in a range of 1-100 mm.…”
Section: Introductionmentioning
confidence: 99%